Dermatological toxicity due to targeted anticancer drugs: A new challenge in Oncology practice - Mohammad Hussain Mir; Rather, Parvaiz; Farhana Siraj Bagdadi (Journal of Pakistan Association of Dermatologists, 2022)
Abstract Background: Although newer targeted therapeutic agents have been introduced to improve the safety profile of cancer chemotherapy, yet new adverse effects, including dermatological adverse effects, have been increasingly reported after their use. Objective: We conducted this study aimed to observe the dermatological adverse effects occurring with commonly used targeted therapeutic agents at our center. Material and method: This hospital based observational descriptive study conducted over a period of more than one year, included prospective adult patients put on newer targeted therapeutic agents for different types of malignancies. Patients with prior cutaneous or other drug hypersensitivity reactions and known liver and kidney diseases were excluded from the study. Results: 24 (21.43%) of 112 patients developed dermatological adverse effects, with 45 adverse effects in all. Most common cutaneous findings were Xerosis/ Pruritus in 7, papulopustular eruptions in 6, Hand foot syndrome and morbilliform eruptions in 3 (10.7%) each and lichenoid eruptions in 2 (7.1) patients. Alopecia in 8, Paronychia in 2, Oral mucositis in 4 patients were the changes seen in hair, nails and mucosae respectively. Conclusion: This study re-emphasized the need to anticipate dermatological adverse effects due to new targeted chemotherapeutic agents. Proper counselling of the patients and their family members and timely management by treating physicians, oncologists and dermatologist can guide towards rationalizing the decision regarding continuation and discontinuation of such vital therapy. Key words: Newer targeted drugs; chemotherapeutic agents; Dermatological adverse effects.